Influence of dolls of reflecting the perfectionist woman’s body on the self-perception of the of 5-6 years old girls - AYSE ALPTEKIN; AYSEGUL SARIKAYA (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research intends to look at how girls aged 5 and 6 feel about their own bodies in relation to the dolls that have become increasingly popular with girls in recent years and are seen as reflecting a perfectionist ideal of the female form that is seen as harmful to the development of children in some countries.Method: Data were gathered using a Turkish version of the "Demoulin Self-Perception Scale" created by Bencik (2006). The study included 50 girls from an independent kindergarten in the province of Konya; 25 were assigned to the experimental group, and the other 25 were assigned to the control group. For eight weeks, the children in the experimental group played with dolls representing the ideal woman’s body for one hour per day, while the children in the control group were assured that they did not play with such dolls.Findings: Findings from this study showed no statistically significant difference in the self-esteem subscale between the study’s intervention and control groups. Simultaneously, the self-efficacy subscale showed a statistically significant difference favoring the control group. The experimental group was given dolls that did not depict the ideal female form to play with for eight weeks after the study concluded. No statistically significant changes were observed between the pre-and post-tests given to the experimental group.Implications/Novel Contribution: This study adds to the existing body of literature by highlighting the negative effects on child development when researchers disrupt children’s natural behavior, such as by prohibiting them from playing with dolls in their natural environment. Since children usually do this in a more natural setting with their friends, it is assumed that this is where the effect is most obvious. This section may contain the developmental intervention for children. Doing this work in the wild and contributing new insights and information to the field sets it apart.